PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT KARTIKA MANDIRI CEMERLANG JAKARTA BARAT - Siti Fadila Eka Syafia; Sam Cay (Al Hasanah Barokah Foundation, 2025)
This research aims to determine the effect of reward and punishment on employee performance at PT. Kartika Mandiri Cemerlang West Jakarta, partially and simultaneously. The method used is a quantitative method. The research sample was 51 respondents. Data analysis methods used in the study include instrument tests consisting of validity tests, reliability tests, classical assumption tests consisting of normality tests, multicollinearity tests, heteroscedasticity tests, multiple linear regression tests, correlation coefficients, determination coefficient tests, hypothesis tests consisting of partial t tests and simultaneous f tests. The results of the study showed that rewards have an effect on employee performance with a t-count value of 11.407 > t table 2.010 with a significance of 0.001 < 0.05, then Ho1 is rejected, Ha1 is accepted. Punishment has a positive and significant effect on employee performance with a t-count value of 3.347 > t table 2.010 with a significance of 0.002 < 0.05, then Ho2 is rejected, Ha2 is accepted. Reward and punishment have a positive and significant influence on employee performance with a calculated F value of 74.355 > Ftable 3.190 with a significant level of 0.001 < 0.05, thus Ho3 is rejected and Ha3 is accepted. The results of the Rsquare value (determination coefficient) of 0.756, it can be concluded that the reward variables (X1) and punishment (X2) simultaneously have a contribution to the influence on employee performance (Y) of 75.6%, while the remaining 24.4% is caused by variables that are not included in this research model.